Fundamentos teóricos del Pensamiento complejo de Edgar Morin - Barberousse, Paulette (Revista Electrónica Educare, 2008)
In face of what he considered as the crisis of the Western paradigm of simplification and disjunction, based on the reduction and separation of knowledge, Edgar Morin posited the emergence of a new paradigm of complexity that would attempt to articulate and contextualize scientific, humanistic, and artistic cultures. To accomplish such purpose, Morin argued for an integration of ideas, concepts and notions drawing on different theoretical sources. Approaching complexity has required a dialectic and creative resignification of the legacy of such theories through a new synthesis that both integrates and surpasses them qualitatively.